New system for vibrating and orientation of steel fibers in masonry mortars. (November 2021) - Morón, Alberto; Ferrández, Daniel; Saiz, Pablo; Álvarez, Manuel; Morón, Carlos
Abstract: The incorporation of reinforcing fibers during the kneading process has become an efficient method to improve the flexural strength of building binder materials. In this work, a new system for the vibration and orientation of metallic fibers has been developed. This allows the fibers to be positioned perpendicular to the direction of the flexural stress. This vibrating system for construction mortars in a fresh state improves the performance of mortars made with recycled aggregate, increasing their mechanical resistance and their application within the building sector. Testswere carried out with mortars made with two types of recycled aggregates and two different percentages of reinforcing fibers. The results show thatby applying the vibrating system implemented, it is possible to increase the mechanical resistance of mortars made with recycled aggregate by more than 15%. Highlights: A new vibrating device to orientate fibers was developed. A comparison between concrete and ceramic aggregate mortars was performed. It was possible to orient more than 50% of the steel fibers content in all the samples made. The orientation of fibers transversely to the load increases the flexural strength of mortars made with recycled aggregate.